The awareness on emergency management of tooth avulsion injury among primary school teachers - Hassan, Haszelini; Mohd. Nor, Hikmah; Ardini, Yunita Dewi; Shamsuri, Norhidayah; Musthapa, Nur Adibah Amani (Zes Rokman Resources, 2018)
Teachers are most likely to be among the first to see a child immediately if dental injury happens at school. Hence, their intervention greatly influences the prognosis of an avulsed tooth. This study assessed the level of knowledge and attitude on the management of tooth avulsion injury among primary school teachers. This cross-sectional study was done using a pretested questionnaire involving 100 teachers of two primary schools in Kuantan. 81 out of 100 teachers understood that an avulsed permanent tooth should be saved. 45% of the respondents thought that they were able to distinguish between deciduous and permanent teeth. Only 24% of respondents were able to answer correctly on immediate action to be taken when they encountered tooth avulsion injury. 81% of respondents knew that an avulsed tooth has to be held by its crown. However, only 18% chose to replant the tooth back into its socket, and 76% agreed that replantation must be done immediately. Regarding the storage medium for the avulsed tooth, 38% chose to place it in ice, followed by tissue paper (32%). Previous experience of witnessing tooth avulsion injury, knowing the importance of emergency management and female gender were found to improve the teachers’ knowledge on emergency protocols (p<0.05). Overall, the level of awareness on emergency management of tooth avulsion injury among primary school teachers was found to be unsatisfactory (81%). Thus, the teachers should be given more exposure and training on the emergency management of tooth avulsion injury at school. The teachers play a key role in preventing detrimental impact to the children’s dentition and psychosocial development due to the loss of permanent tooth.